Modified Graphitic Carbon Nitride Nanosheets for Efficient Photocatalytic Hydrogen Evolution. Issue 22 (17th October 2019) - Zhou, Xunfu; Zhu, Yating; Gao, Qiongzhi; Zhang, Shengsen; Ge, Chunyu; Yang, Siyuan; Zhong, Xinhua; Fang, Yueping
Abstract: Considerable research efforts have been devoted to develop noble‐metal‐free cocatalysts coupled with semiconductors for highly efficient photocatalytic H2 evolution as part of the challenge toward solar‐to‐fuel conversion. Herein, a new cocatalyst with excellent activity in the electrocatalytic H2 evolution reaction (HER) that is based on Co sheathed in N‐doped graphitic carbon nanosheets (Co@NC) was fabricated by a surfactant‐assisted pyrolysis approach and then coupled with g‐C3 N4 nanosheets to construct a 2 D‐2 D g‐C3 N4 /Co@NC composite photocatalyst by a simple grinding method. As a result of advantages in effective electrocatalytic HER activity, suitable electronic band structure, and rapid interfacial charge transfer brought about by the 2 D‐2 D spatial configuration, the g‐C3 N4 /Co@NC photocatalyst that contained 4 wt % Co@NC presented a high photocatalytic H2 generation rate of 15.67 μmol h −1 under visible‐light irradiation ( λ ≥400 nm), which was 104.5 times higher than that of pristine g‐C3 N4 . The optimum g‐C3 N4 /Co@NC photocatalyst showed a high apparent quantum efficiency of 10.82 % at λ =400 nm. Abstract : Cobalt cocatalyst combination : A ternary g‐C3 N4 /Co@NC photocatalytic system, prepared by the judicious integration of a 2 D Co@NC (graphene‐like nanosheets) cocatalyst and 2 D g‐C3 N4 photocatalyst, is used for efficient hydrogen evolution in triethanolamine solution or pure water.